1,N6-ethenodeoxyadenosine and 3,N4-ethenodeoxycytidine in liver DNA from humans and untreated rodents detected by immunoaffinity/32P-postlabelling - Nair, Jagadeesan; Barbin, A.; Guichard, Y.; Bartsch, Helmut (Carcinogenesis, 1995)
The etheno-bridged exocyclic DNA adducts 1,N6-ethenodeoxyadenosine (εdA) and 3, N4-ethenodeoxycytine (εdC) can be formed by several structurally diverse carcinogens and mutagens that include vinyl chloride and urethane. In order to investigate the occurrence and persistence of these adducts in rodents exposed to such DNA-damaging agents, an ultra-sensitive detection method has been developed. It is based on immunoaffinity purification of the etheno adducts and subsequent 32P-postlabelling followed by separation as 5'-monophosphates on polyethyleneimine-cellulose-coated thin-layer plates. Normal nucleotides in the DNA samples were quantitated by HPLC. Optimal conditions for enzymatic hydrolysis of DNA are described: deoxyuridine 3'-monophosphate was used as internal standard to correct for labelling efficiency of the etheno adducts. The method had a detection limit of 25 amol of εdA and εdC for a 50 μg DNA sample. Using this technique, analysis of liver DNA from humans with unknown exposure revealed the presence of εdA and εdC residues in the range of 0-27 adducts per 109 parent bases. Liver DNA obtained from untreated mice and rats was also shown to contain similar low but variable levels of these etheno adducts. In vitro studies indicated that these promutagenic DNA lesions could arise from endogenously formed lipid peroxidation products.